Fabrication and Characterization of Al6061-Nano Al2O3 Composites by Ultrasonic Assisted Stir Casting followed by Heat Treatment and Hot Forging - Rajesh Purohit; M.M.U. Qureshi; Ashish Kumar; Abhishek Mishra; R.S. Rana (Archives of Metallurgy and Materials, 2023)
The present work comprises the development of Al6061/nano Al2O3 composites with 0 to 4 weight percent in steps of 0.5 wt. % of nano alumina particles by using ultrasonic assisted stir casting. Casted samples were subjected to heat treatment and hot forging. Further forged and heat-treated gear blanks of nano Al2O3 (0 to 3.0 weight %) reinforced nanocomposites were machined to make spur gears for the wear test. The results have shown that nano Al2O3 reinforcement in the Al6061 matrix with heat treatment and forging improves the hardness and compressive strength up to 3.5 wt. %, after that, it starts decreasing because of the agglomeration of nano alumina particles. SEM results reveal grain refinement of the pure alloy after reinforcement. Removal of porosity and voids observed after forging operation. Wear resistance increasing with incorporation of Al2O3 nanoparticles in base alloy, reinforcement wt. %, precipitation hardening and hot forging also improves wear resistance and mechanical properties. These composites have widespread applications in gear, brake discs, crankshaft, clutch plates, pistons, and other components of automobiles and aircraft structures.